Epidemiology of Extended-Spectrum Beta-Lactamase and Carbapenemase-Producing Enterobacterales in the Greater Mekong Subregion: A Systematic-Review and Meta-Analysis of Risk Factors Associated With Extended-Spectrum Beta-Lactamase and Carbapenemase Isolation - Singh, Shweta R.; Teo, Alvin Kuo Jing; Prem, Kiesha; Ong, Rick Twee-Hee; Ashley, Elizabeth A.; van Doorn, H. Rogier; Limmathurotsakul, Direk; Turner, Paul; Hsu, Li Yang (Frontiers in Microbiology, 2021)
Background: Despite the rapid spread of extended-spectrum beta-lactamase (ESBL) producing-Enterobacterales (ESBL-E) and carbapenemase-producing Enterobacterales (CPE), little is known about the extent of their prevalence in the Greater Mekong Subregion (GMS). In this systematic review, we aimed to determine the epidemiology of ESBL-E and CPE in clinically significant Enterobacterales: Escherichia coli and Klebsiella pneumoniae from the GMS (comprising of Cambodia, Laos, Myanmar, Thailand, Vietnam and Yunnan province and Guangxi Zhuang region of China). Methods: Following a list of search terms adapted to subject headings, we systematically searched databases: Medline, EMBASE, Scopus and Web of Science for articles published on and before October 20th, 2020. The search string consisted of the bacterial names, meth-ods involved in detecting drug-resistance phenotype and genotype, GMS countries, and ESBL and carbapenemase detection as the outcomes. Meta-analyses of the association between the isolation of ESBL from human clinical and non-clinical specimens were performed using the 'METAN' function in STATA 14. Results: One hundred and thirty-nine studies were included from a total of 1513 identified studies. Despite the heterogeneity in study methods, analysing the prevalence proportions on log-linear model scale for ESBLproducing-E. coli showed a trend that increased by 13.2% (95%CI:6.1-20.2) in clinical blood specimens, 8.1% (95%CI: 1.7-14.4) in all clinical speci-mens and 17.7% (95%CI: 4.9-30.4) increase in carriage specimens. Under the log-linear model assumption, no significant trend over time was found for ESBLproducing K. pneu-moniae and ESBL-E specimens. CPE was reported in clinical studies and carriage studies past 2010, however a trend could not be determined because of the small dataset. Twelve studies were included in the meta-analysis of risk factors associated with isolation of ESBL. Recent antibiotic exposure was the most studied variable and showed a significant positive association with ESBL-E isolation (pooled OR:2.9, 95%CI:2.3-3.8) followed by chronic kidney disease (pooled OR: 4.7, 95%CI: 1.8-11.9), and other co-morbidities (pooled OR:1.6, 95%CI: 1.2-2.9). Conclusions: Data from GMS is heterogeneous with significant data-gaps, especially in community settings from Laos, Myanmar, Cambodia and Yunnan and Guangxi provinces of China. Collaborative work standardising the methodology of studies will aid in better moni-toring, surveillance and evaluation of interventions across the GMS.